An Arabidopsis mutant deficient in phosphatidylinositol-4-phosphate kinases ß1 and ß2 displays altered auxin-related responses in roots - Starodubtseva, Anastasiia; Kalachova, Tetiana; Retzer, Katarzyna; Jelínková, Adriana; Dobrev, Petre; Lacek, Jozef; Pospíchalová, Romana; Angelini, Jindřiška; Guivarc'h, Anne; Pateyron, Stéphanie; Soubigou-Taconnat, Ludivine; Burketová, Lenka; et al. (Scientific reports, 2022)
Phosphatidylinositol 4-kinases (PI4Ks) are the first enzymes that commit phosphatidylinositol into the phosphoinositide pathway. Here, we show that Arabidopsis thaliana seedlings deficient in PI4Kβ1 and β2 have several developmental defects including shorter roots and unfinished cytokinesis. The pi4kβ1β2 double mutant was insensitive to exogenous auxin concerning inhibition of root length and cell elongation; it also responded more slowly to gravistimulation. The pi4kß1ß2 root transcriptome displayed some similarities to a wild type plant response to auxin. Yet, not all the genes displayed such a constitutive auxin-like response. Besides, most assessed genes did not respond to exogenous auxin. This is consistent with data with the transcriptional reporter DR5-GUS. The content of bioactive auxin in the pi4kß1ß2 roots was similar to that in wild-type ones. Yet, an enhanced auxin-conjugating activity was detected and the auxin level reporter DII-VENUS did not respond to exogenous auxin in pi4kß1ß2 mutant. The mutant exhibited altered subcellular trafficking behavior including the trapping of PIN-FORMED 2 protein in rapidly moving vesicles. Bigger and less fragmented vacuoles were observed in pi4kß1ß2 roots when compared to the wild type. Furthermore, the actin filament web of the pi4kß1ß2 double mutant was less dense than in wild-type seedling roots, and less prone to rebuilding after treatment with latrunculin B. A mechanistic model is proposed in which an altered PI4K activity leads to actin filament disorganization, changes in vesicle trafficking, and altered auxin homeostasis and response resulting in a pleiotropic root phenotypes.
Keywords: kořeny rostlin; Phosphatidylinositols; Indoleacetic Acids; fosfatidylinositolfosfáty; Arabidopsis Proteins; Plant Roots; kyseliny indoloctové; Phosphatidylinositol Phosphates; Arabidopsis; proteiny huseníčku; fosfatidylinositoly